Triple Bioluminescence Imaging for In Vivo Monitoring of Cellular Processes - Casey A Maguire; M Sarah Bovenberg; Matheus HW Crommentuijn; Johanna M Niers; Mariam Kerami; Jian Teng; Miguel Sena-Esteves; Christian E Badr; Bakhos A Tannous (Elsevier, 2013)
Bioluminescence imaging (BLI) has shown to be crucial for monitoring in vivo biological processes. So far, only dual bioluminescence imaging using firefly (Fluc) and Renilla or Gaussia (Gluc) luciferase has been achieved due to the lack of availability of other efficiently expressed luciferases using different substrates. Here, we characterized a codon-optimized luciferase from Vargula hilgendorfii (Vluc) as a reporter for mammalian gene expression. We showed that Vluc can be multiplexed with Gluc and Fluc for sequential imaging of three distinct cellular phenomena in the same biological system using vargulin, coelenterazine, and D-luciferin substrates, respectively. We applied this triple imaging system to monitor the effect of soluble tumor necrosis factor-related apoptosis-inducing ligand (sTRAIL) delivered using an adeno-associated viral vector (AAV) on brain tumors in mice. Vluc imaging showed efficient sTRAIL gene delivery to the brain, while Fluc imaging revealed a robust antiglioma therapy. Further, nuclear factor-κB (NF-κB) activation in response to sTRAIL binding to glioma cells death receptors was monitored by Gluc imaging. This work is the first demonstration of trimodal in vivo bioluminescence imaging and will have a broad applicability in many different fields including immunology, oncology, virology, and neuroscience.